2021
DOI: 10.1364/prj.416815
|View full text |Cite
|
Sign up to set email alerts
|

Optical fiber SPR biosensor complying with a 3D composite hyperbolic metamaterial and a graphene film

Abstract: In the present study, an optical fiber surface plasmon resonance (SPR) biosensor was developed for measuring time- and concentration-dependent DNA hybridization kinetics. Its design complies with a 3D Au / Al 2 O 3 multilayer composite hyperbolic metamaterial (HMM), a graphene film, and a D-shaped plastic optical fiber. According to the numerical simulation and the experimental demonstration, the SPR peak of the designed biosensor can be effectively altered i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 52 publications
0
19
0
1
Order By: Relevance
“…This allows the angular detection of large-molecular-weight biomolecules such as Cowpea mosaic virus (5 × 10 6 Da) at concentrations as low as 1 fM. Hyperbolic metamaterial-based biochemical sensors can be further miniaturized by integrating the metamaterials with optical fibers, such as D-shaped fibers. …”
Section: Optical Sensing With Plasmonic Metamaterialsmentioning
confidence: 99%
“…This allows the angular detection of large-molecular-weight biomolecules such as Cowpea mosaic virus (5 × 10 6 Da) at concentrations as low as 1 fM. Hyperbolic metamaterial-based biochemical sensors can be further miniaturized by integrating the metamaterials with optical fibers, such as D-shaped fibers. …”
Section: Optical Sensing With Plasmonic Metamaterialsmentioning
confidence: 99%
“…Since then, many HMMs and HMs have been proposed for high-sensitivity sensing. [16][17][18][19][20][21] Recently, our research group combined electron beam lithography and electrochemical methods to fabricate an NHMM sensor, achieving a record sensitivity of 41 600 nm RIU À1 . 22 HMMs exhibit anisotropic optical properties and involve complex mode relationships, and the effective excitation of the BPP modes in HMMs for highly sensitive sensing is an important matter.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, many HMMs and HMs have been proposed for high-sensitivity sensing. 16–21 Recently, our research group combined electron beam lithography and electrochemical methods to fabricate an NHMM sensor, achieving a record sensitivity of 41 600 nm RIU −1 . 22…”
Section: Introductionmentioning
confidence: 99%
“…Hyperbolic metamaterials (HMMs) have hyperbolic dispersions by the opposite permittivity components and can be adjusted by changing the periodic structure parameters. , Our previous work demonstrated that coating an HMM onto a side-polishing fiber sensor can effectively improve the SPR sensitivity to 9000 nm per refractive index unit (nm/RIU) with an optimal figure of merit (FOM) of 230.8 RIU –1 . Similarly, Li et al reported that HMM combined with plastic-clad fibers could achieve a sensitivity of 4461 nm/RIU for DNA detection . Although the high RI sensitivities of HMM-based SPR (H-SPR) sensors showed potential for temperature sensing, such reports have rarely been seen yet.…”
Section: Introductionmentioning
confidence: 99%